2022
DOI: 10.1007/s00432-022-03986-3
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific effects of NOX4 inactivation in acute myeloid leukemia (AML)

Abstract: Purpose Oxidative stress has been linked to initiation and progression of cancer and recent studies have indicated a potential translational role regarding modulation of ROS in various cancers, including acute myeloid leukemia (AML). Detailed understanding of the complex machinery regulating ROS including its producer elements in cancer is required to define potential translational therapeutic use. Based on previous studies in acute myeloid leukemia (AML) models, we considered NADPH oxidase (NOX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Hole et al [87] reported that the constitutive activation of NOXs caused the generation of extracellular ROS to be significantly augmented in more than 60% of patients with AML and that the increased ROS prompted the proliferation of AML cells, as well as normal CD34 + cells, to a lesser extent. Demircan et al [88] analyzed the important role of the NOX family member NOX4 in AML using human AML cells and mouse models. They revealed that the proliferation ability and cell competition were reduced in fmslike receptor tyrosine kinase 3-internal tandem duplication (FLT3-ITD)-positive human AML cells upon inhibition of the enzymatic activity of NOX4 and p22 phox .…”
Section: Nadph Oxidase (Nox) Family Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hole et al [87] reported that the constitutive activation of NOXs caused the generation of extracellular ROS to be significantly augmented in more than 60% of patients with AML and that the increased ROS prompted the proliferation of AML cells, as well as normal CD34 + cells, to a lesser extent. Demircan et al [88] analyzed the important role of the NOX family member NOX4 in AML using human AML cells and mouse models. They revealed that the proliferation ability and cell competition were reduced in fmslike receptor tyrosine kinase 3-internal tandem duplication (FLT3-ITD)-positive human AML cells upon inhibition of the enzymatic activity of NOX4 and p22 phox .…”
Section: Nadph Oxidase (Nox) Family Proteinsmentioning
confidence: 99%
“…Demircan et al. [ 88 ] analyzed the important role of the NOX family member NOX4 in AML using human AML cells and mouse models. They revealed that the proliferation ability and cell competition were reduced in fms-like receptor tyrosine kinase 3-internal tandem duplication (FLT3-ITD)-positive human AML cells upon inhibition of the enzymatic activity of NOX4 and p22 phox .…”
Section: Source Of Ros Generation In Hematopoietic Cellsmentioning
confidence: 99%
“…Monocytes and macrophages generate high levels of superoxides through NOX as a part of their microbicidal mechanisms. Different members of the NOX family have been reported to be associated with the development of various cancers such as acute myeloid leukemia, 7 gastric cancer, 8 and hepatocellular carcinoma 9 . The peroxisome is a dynamic organelle involved in various metabolic processes such as fatty acid α ‐ and β oxidation, amino acid catabolism, and the glyoxylate cycle.…”
Section: Changes In Cellular Ros Generation and Mitophagy In Cscsmentioning
confidence: 99%
“…The two primary sources of ROS in tumor cells are the mitochondrial respiratory chain and NOX 17,18 . The NOX protein family consists of seven enzyme complexes, including NOX1‐5 and two related dual oxidases (DUOX1‐2) 19 . We review recent studies on oxidative stress and redox homeostasis in AML, with the urgency to find new therapies to target relapsed/chemoresistant AML cells susceptible to the latest drugs.…”
Section: Introductionmentioning
confidence: 99%